Actualization of the Role of Digital Citizenship: Solution to the Threat of Cyber Gambling Chaos for Sustainable Development Goals (SDG's) in Indonesia - Khamdan Safiudin; Nur Hayati (Universitas Negeri Surabaya, 2025)
The rise of cyber gambling in Indonesia has posed a serious threat to various aspects of people's lives, especially affecting the country's sustainable development goals or commonly referred to as SDG's. The proliferation of online gambling platforms has led to a significant increase in financial transactions, with a sharp increase in the total value of online gambling transactions. The negative impacts of cyber gambling not only cause financial losses, but also affect productivity, social costs, health problems, and even the risk of money laundering. In addition, the prevalence of gambling among adolescents and vulnerable populations highlights the urgent need for comprehensive solutions to combat this growing threat. Digital citizenship plays a vital role in preventing cyber gambling by encouraging ethical behavior and responsible use of technology. Increasing digital literacy through formal education and public awareness campaigns is essential in raising awareness of the risks associated with online gambling. By integrating digital citizenship principles into curriculum development and media regulation, individuals can better protect themselves from exposure to online gambling activities. Leveraging advanced technologies such as artificial intelligence can help early detection and blocking of gambling-related content, while coordination with government agencies and international cooperation can strengthen law enforcement efforts against online gambling syndicates. By taking a proactive stance towards digital citizenship and implementing comprehensive policy measures, Indonesia can effectively address the challenges posed by cyber gambling and contribute to achieving sustainable development goals.